Infinite tension limit of the pure spinor superstring - Berkovits, Nathan [UNESP] (Springer Nature, 2014)
Mason and Skinner recently constructed a chiral infinite tension limit of the Ramond-Neveu-Schwarz superstring which was shown to compute the Cachazo-He-Yuan formulae for tree-level d = 10 Yang-Mills amplitudes and the NS-NS sector of tree-level d = 10 supergravity amplitudes. In this letter, their chiral infinite tension limit is generalized to the pure spinor superstring which computes a d = 10 superspace version of the Cachazo-He-Yuan formulae for tree-level d = 10 super-Yang-Mills and supergravity amplitudes. © 2014 The Author(s).
Keywords: Scattering Amplitudes; Superstrings and Heterotic Strings